High frequency of vertebral fracture and low bone quality in patients with rheumatoid arthritis—Results from TOMORROW study. Issue 3 (4th May 2017) - Okano, Tadashi; Inui, Kentaro; Tada, Masahiro; Sugioka, Yuko; Mamoto, Kenji; Wakitani, Shigeyuki; Koike, Tatsuya; Nakamura, Hiroaki
Abstract: Objectives : Osteoporosis is one of the complications in patients with rheumatoid arthritis (RA). In this study, we researched the morbidity of existing vertebral fractures and the risk factors for vertebral fractures in patients with RA. Methods : This study included 413 participants, 208 patients with RA, and 205 age- and sex-matched controls without RA. Clinical data, radiographic assessment of vertebral fracture from T4 to L4 in thoracic and lumber spine, bone mineral density (BMD), and bone metabolic markers (BMM) were analyzed. Results : Vertebral fractures were observed more frequently, severe and multiple in patients with RA. In the logistic regression analysis, age (adjusted odds ratios (OR): 1.07, 95% confidence interval (CI): 1.04–1.09) and RA (adjusted OR: 1.72, 95% CI: 1.04–2.83) were risk factors for existing vertebral fracture. Moreover, two bone matrix-related markers, undercarboxylated osteocalcin (ucOC) (adjusted OR: 1.68, 95% CI: 1.02–2.78), and urinary pentocidine (adjusted OR: 2.51, 95% CI: 1.48–4.24) were associated with existing vertebral fracture. Conclusions : High frequent, multiple, and severe vertebral fractures were found in patients with RA compared to the controls. Low bone quality might be the cause of the frequent prevalence of vertebral fracture in patients with RA.